Efektifitas penyuluhan kesehatan tentang pengelolaan DAGUSIBU obat pada mahasiswa Jurusan Farmasi Poltekkes Kemenkes Aceh - Amelia Sari; Defri Aroni; Maria Irwani; Burdah Burdah; Halimatussakdiah Halimatussakdiah (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: One of the ways of good drug management is DAGUSIBU (Get, Use, Store, and Dispose of), which describes the procedure for managing drugs from the beginning of obtaining to when the drug is no longer consumed and finally disposed of. A program from Indonesian Pharmacists to educate the public on how to use drugs properly. Selection of final year pharmacy students to prepare pharmacy who can provide excellent and correct education.Objectives: The study aims to determine the knowledge of students of the Department of Pharmacy of the Health Polytechnic of the Ministry of Health of Aceh after counseling about DAGUSIBU.Methods: The study used a Quasi Experiment design. The sample was selected using a total sampling technique with a sample of 85 students. This research was conducted in October 2022 at the Department of Pharmacy of the Health Polytechnic of the Ministry of Health of Aceh. Data collection using a questionnaire measuring instrument by filling out a google form. Data processing is carried out in stages, from editing, coding, entry, and cleaning data. Data analysis was performed descriptively and analytically using the Dependent T-test.Results: The study's results are based on the level of knowledge of students of the Department of Pharmacy, Health Polytechnic of Aceh, Ministry of Health. Before being given health counseling on the management of DAGUSIBU the most were in the excellent category, as many as 55 people (64,7%), and in the poor category, as many as 30 people (35,3%), while the level of knowledge after being given health counseling on the management of DAGUSIBU the most were in the excellent category as many as 76 people (89,4%) while in the poor category as many as nine people (10,6%).Conclusion: There is effectiveness after health counseling on managing DAGUSIBU drugs in students at the Department of Pharmacy, Health Polytechnic of Aceh, Ministry of Health.